A Comparative Bibliometric Analysis of Global Research on Adaptation Interventions for Healthy Aging at Home - Wusi Zhou; Xiaoyang Lyu; Yuxi Huang; Biya Jiang; Jianzhong Jiang (SAGE Open)
Housing adaptation is recognized as a rehabilitation intervention that makes modifications to the physical environment for older people active aging at home. However, the current delivery of adaptation is centered on a reactive approach that modifies the home when an individual get to crisis. This study aimed to assess the contribution of housing adaptation research outputs across the world and disclose housing adaptation as a public issue not just a private trouble. A comparative bibliometric approach was adopted. All available publications on housing adaptation for healthy aging between 2006 and 2022 in the Web of Science Core Database was retrieved and reviewed systematically. CiteSpace software was first performed to generate a knowledge network, this was followed by HistCite analysis to gain chronological historiographs. There has been a gradual increase of housing adaptation research papers since 2006, with a total of 406 published by 116 journals in 2022. 1,152 authors from 672 institutions in 42 countries have been involved. Housing adaptation has been given research priority in some countries like the US, the UK and Sweden. However, cooperation between researchers is subject to the regional level. Researchers from different countries and institutions came into this scientific field, the dynamic research process can be divided into three stages. Housing adaptation is a public issue in need of expanded interdisciplinary research worldwide. International collaboration will help developing countries to tackle the challenges in the provision of housing adaptation. A gradual shift from reactive towards proactive will encourage an earlier adaptation intervention to maximize inclusive living.